Balaenoptera acutorostrata Lacepede 1804 - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Balaenoptera acutorostrata Lacépède, 1804 —Common Minke Whale Balaenoptera acuto-rostrata Lacépède, 1804 p.134; Type locality- France; Kuroda, 1938 p.11. B. acutorostrata : Won, 1958 p.433; Won, 1967 p.78; Won, 1968 p.240; Kim et al ., 2000 p.60; Kim, 2004 p.222. Range: Balaenoptera acutorostrata consistently inhabits the East Sea and Yellow Sea (Fig. 75). Observations peak in spring followed by autumn, during migration. This species swims primarily in the mid-Yellow Sea and continental shelf of the East Sea but rarely comes into the coastal waters of Korea. Remarks: The subspecies B. a. scammoni Deméré, 1986 was assigned to the population living in the North Pacific Ocean. However, the population of B. acutorostrata in the East Sea between Korea and Japan might represent a new subspecies (Archer et al . 2013). Conservation status: All populations of this species are included in CITES Appendix I (except the population in the waters of West Greenland is included in Appendix II). Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on pages 115-116, DOI:10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198